Department Head Leadership Style Strategy In Complex Management (Case Study of the Head of the Department of Teacher Education Leadership Madrasah Ibtidaiyah Walisongo) - Shanie, Arsan; Wahyudin, Wahyudin; Rusdarti, Rusdarti; Abrini, Mintarsih (Proceedings of International Conference on Science, Education, and Technology, 2024)
This study aims to describe the leadership strategies of department leaders in complex management. This qualitative research uses a case study approach as the main research design. The main research subject is the Head of the PGMI Department of UIN Walisongo Semarang Campus. The data collection techniques in this study used were in-depth interview techniques, participatory observation, and document analysis. Data analysis techniques include data reduction, displaying data, drawing conclusions, and verifying data. The results of this study are the leadership style strategies of department leaders in complex management: 1) Application of Transformational Leadership Style to Inspire and Encourage Innovation 2) Development of Expertise and Skills to improve communication skills and conflict management skills for lecturers and staff; 3) Use of participatory style. Deliberation in decision-making and adopting shura principles in overcoming conflicts; 4) Facilitating Open Discussion, i.e., Encouraging lecturers and staff to participate in open discussions to identify and respond to conflicts early; 5) The application of Islamic leadership ethics; 6) Recognize the appropriate leadership style in conflict resolution; 7) Educational approach, 8) Continuous evaluation and update.